New taxonomic and faunistic data on the funnel-weavers (Araneae, Agelenidae) of Turkiye and the Caucasus, with five new species - Zamani, Alireza; Kaya, Rahşen S.; Marusik, Yuri M. (Pensoft Publishers, 2025)
New taxonomic and faunistic data on the agelenid spiders of Turkiye and the Caucasus are provided. Five species are described as new to science: Maimuna antalyensis sp. nov. (♂♀; Turkiye: Antalya), Tegenaria ballarini sp. nov. (♂♀; Turkiye: Antalya), T. beyazcika sp. nov. (♂; Turkiye: Antalya), T. egrisiana sp. nov. (♂♀; Georgia: Imereti), and T. hoeferi sp. nov. (♂♀; Armenia: Kotayk). Tegenaria lazarovi Dimitrov, 2020, syn. nov. is proposed as a new junior synonym of T. averni Brignoli, 1978. Persiscape caucasica (Guseinov, Marusik & Koponen, 2005) is newly reported from Armenia, and T. chumachenkoi Kovblyuk & Ponomarev, 2008 is reported for the first time from Turkiye. New distribution records for T. dalmatica Kulczyński, 1906, T. hamid Brignoli, 1978, T. longimana Simon, 1898 and T. percuriosa Brignoli, 1972, and topotype material for T. tekke Brignoli, 1978 are reported. The record of Eratigena fuesslini (Pavesi, 1873) from Turkiye is found to be based on a misidentification, and is herein attributed to T. hamid. The presence of an embolic spine, unknown in any other species of Tegenaria, is documented in T. anhela Brignoli, 1972 for the first time. Photographs are provided for all treated species.